حروف الجر في كتاب رياض الصالحين: دراسة نحوية تحليلية - Muhammad Najmi bin Md Aziman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines the book written by Imam Abu Zakaria bin Sharaf Al-Nawawi, Riyad al-Salihin and focuses on the various aspects of preposition, including its factors, characteristics, functions as well as meanings. This book is one of the most comprehensive books relating to belligerent disbelief, divine warning and various types of ethics. It is a compilation of authentic hadiths narrated by the Prophet Muhammad p.b.u.h. It includes all aspects of life in this temporary world as well as the journey to Hereafter. The purpose of this research is to identify the grammatical and statistical descriptive characters with the semantic aspects of prepositions mentioned in the book of Riyad al-Salihin, where an individuated preposition signifies more than four different connotations. These cause difficulties in defining its exact meaning in the complete sentences and may result to the misinterpretation of the intended syntax. The process of determining the meanings of prepositions within the syntax requires many examples to measure them. In order to achieve this objective, the research employs the descriptive, statistical and analytical approaches. The research focuses on the words uttered by Prophet Muhammad p.b.u.h and puts them in the perspective of a statistical analysis.